5x+6=x+22

Simple and best practice solution for 5x+6=x+22 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+6=x+22 equation:


Simplifying
5x + 6 = x + 22

Reorder the terms:
6 + 5x = x + 22

Reorder the terms:
6 + 5x = 22 + x

Solving
6 + 5x = 22 + x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-1x' to each side of the equation.
6 + 5x + -1x = 22 + x + -1x

Combine like terms: 5x + -1x = 4x
6 + 4x = 22 + x + -1x

Combine like terms: x + -1x = 0
6 + 4x = 22 + 0
6 + 4x = 22

Add '-6' to each side of the equation.
6 + -6 + 4x = 22 + -6

Combine like terms: 6 + -6 = 0
0 + 4x = 22 + -6
4x = 22 + -6

Combine like terms: 22 + -6 = 16
4x = 16

Divide each side by '4'.
x = 4

Simplifying
x = 4

See similar equations:

| 1/3(2x+4)+5=-2/3(x+1) | | 6.25x+12=30.75 | | 2/3(4x-10) | | 9v-6=5v+18 | | (6x+15)/4=-15x-25+(5/4) | | 8-9(3-k)=14k-11 | | 10[3p+4]-1=49 | | 1/3(2x-1)+1/4(1/2-3x)=-2 | | 5x+21=2x+25 | | 8y-5y-15=32.79 | | 6.25x+12x=30.75 | | 6x-8=x-33 | | 5x-140=63-2x | | 9=w/37 | | X-3+2x-5= | | -18.92-15.8q=-14.97-15.3q | | 7(w-5)=-28 | | 1/2x+6-2x+1/2+7/2 | | 3.5(2x+1.8)-2(2.3x+5)=8.9 | | 320+80m=7280-220m | | 11x-64=26+8x | | 10y-7y-12=46.86 | | 989-m= | | -2p+10=4(-2p-5) | | -134+3x=-5x+90 | | 6.25x+30.75=12 | | 4-3(x+3)+1=2 | | 8x-9x+6=-4 | | 15(t+2)+6t=6 | | 6k+8=3-16k | | ?3(2x?3)=(?6x+9) | | -(3x-3)-(2x-6)+3=-5(x-1)-(3x+2)+3 |

Equations solver categories